Dynamic Rendition of Adipose Genes Under Epigenetic Regulation: Revealing New Mechanisms of Obesity Occurrence - Weijing Wen; Simeng Gu; Fanjia Guo; Zhijian Chen; Sujun Yan; Zhe Mo (Current Issues in Molecular Biology)
Obesity is a chronic metabolic disorder and a growing global public health challenge, affecting hundreds of millions of individuals worldwide. While diet and physical activity are well-established contributors, increasing evidence underscores the critical role of epigenetic mechanisms in mediating obesity-related processes. Epigenetic modifications—such as DNA methylation, RNA methylation (particularly N6-methyladenosine), histone modifications, non-coding RNAs, and chromatin remodeling—modulate gene expression without altering the DNA sequence. This review aims to provide an overview of the epigenetic mechanisms involved in obesity, with an emphasis on their molecular functions and regulatory networks. Integrating findings from relevant studies, we discuss how these modifications influence obesity-related outcomes through regulating key processes such as adipocyte differentiation and energy metabolism. Advancing our understanding of epigenetic regulation may pave the way for novel, targeted strategies in the prevention and treatment of obesity.